Avaliação do desenvolvimento cardíaco neonatal em cordeiros - Ulian, Carla Maria Vela [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
During the first month of life occur the main cardiocirculation adaptations that allow individuals to reach adulthood. This work aimed to describe the possible differences in the heart of the newborn from the cardiac assessment in the Ile de France breed lambs during the first 35 days of age, providing data that may be useful in veterinary medicine and in the different experimental protocols of medicine, which uses this species as a model. Cardiac evaluations were carried out weekly by electrocardiogram and ambulatory electrocardiogram/Holter system, echodopplercardiografic parameters, cardiac silhouette and determination of VHS (vertebral heart size) by radiography, systemic arterial pressure by Doppler and oscillometric method. Twenty clinically healthy lambs were used into the neonatal period. For the rate values of the heart, breath and cardiac silhouette size was observed decrease as age increase. Invasive pressure obtained in normotension (70 mmHg) averaged was 119.14 ± 23.59 mmHg. In comparison between the methods above with the invasive showed that the measurement as overrated in Doppler about 4.24 mmHg (+4%) and 16.56 mmHG (+16%) with the oscillometric method. The echodopplercardiogram analysis was HR between 212 and 134 bpm from birth to 35th day. The aorta diameter (Ao), left atrium (LA), left ventricular diameter in end-diastole (LVd), end-diastole diameter (EDD), end-systole diameter (ESD), left ventricular wall thickness diastole (LVWd), septum E point (SEP) showed progressive increase when compared to birth. The relationship LA:Ao did not suffer significant change until the end of the study, as well as the ejection fraction and shortening (EF and FS). In the DII derivation in the frontal plane of the electrocardiogram was observed difference with decreased from the seventh day in the duration of the PR interval and T wave, and the amplitude of the wave P, R and T. The QT interval ...

Durante o primeiro mês de vida ocorrem as principais adaptações cardiocirculatórias que permitirão ao indivíduo chegar à vida adulta. Este trabalho visou descrever as possíveis diferenças no coração de um recémnascido a partir da avalição cardíaca em cordeiros durante os primeiros 35 dias de idade, fornecendo dados que poderão ser úteis na Medicina Veterinária e nos diversos protocolos experimentais da Medicina, que utiliza os ovinos como modelo. Foram realizadas avaliações cardíacas semanais que consistiram em: eletrocardiograma e eletrocardiograma ambulatorial/sistema Holter, parâmetros ecodopplercardiográficos, exame radiográfico cardíaco, pressão arterial sistêmica (por método Doppler e oscilométrico). Utilizou-se 20 cordeiros, clinicamente saudáveis abrangendo o período neonatal. Para os valores da frequência cardíaca, respiratória e tamanho da silhueta cardíaca, foram observadas diminuições com o passar da idade. A pressão invasiva obtida em normotensão (70 mmHg) teve média de 119,14 ± 23,59 mmHg. Na comparação entre os métodos com a invasiva, pode-se observar que a aferição como Doppler superestimou em 4,24 mmHg (+4%) e em 16,56 mmHg (+16%) com o método oscilométrico. Quanto aos resultados do ecodopplercardiograma, o diâmetro da aorta (Ao), átrio esquerdo (AE), o diâmetro do ventrículo esquerdo no final da diástole (DVEFD), diâmetro no final da diástole (DFD), diâmetro no final da sístole (DFS), espessura da parede livre do ventrículo esquerdo na diástole (EPLVED) e separação entre o ponto E e o septo (SSPE) apresentaram aumento progressivo quando comparado ao nascimento. A relação AE:Ao não sofreu alteração significativa até o final do estudo, assim como a fração de ejeção e encurtamento (FE% e ΔD%). Na derivação DII no plano frontal do eletrocardiograma observou-se diferença com diminuição a partir do sétimo dia na duração do intervalo PR e da onda T, e na...
Evaluation of heart development in neonatal lambs
Keywords: Ovino; Neonatologia veterinária; Pressão arterial; Ecocardiografia; Variabilidade do batimento cardíaco; Torax - Radiografia; Veterinary neonatology